Primary Ocular Transmissible Venereal Tumor in a Prepubescent Female Dog - Couto de Amaral, Andréia Vitor; Mucha, Francine; de Oliveira, Igor Borges; de Carvalho, Camila Franco; de Ataide, Wanessa Ferreira; Saturnino, Klaus Casaro (Acta Scientiae Veterinariae, 2020)
Background: Canine transmissible venereal tumor (CTVT) is a peculiar neoplasm resulting from the transmission of host cancerous cells to another canid by implantation. Transmission occurs among reproductive age dogs, especially those with unrestricted sexual activity. It usually occurs on the external genitalia of dogs and other areas are unusual. However, implants have been described in injured mucosa, as well as metastases in lymph nodes, spleen, skin, anus and perianal space, oral mucosa, nasal mucosa, eyeball and brain. The purpose of this report is to describe the first case of exclusively extragenital ocular CTVT in a prepubescent female dog. Case: A 6-month-old mixed-breed, non-spayed and prepubescent female dog, showing a fast-growing reddish-colored mass in the right eye (RE), was examined. Blepharospasm, mild serosanguineous secretion, chemosis and a smooth surface reddish mass with 2.5 cm in length occupying the orbital area were observed during physical examination, impairing the visualization of the right eyeball. For ocular ultrasonography examination of the affected eye, acepromazine was used (0.03 mg/kg) associated with methadone (0.3 mg/kg) intramuscularly, and propofol (4 mg/kg) for induction and 0.2 mg/kg for maintenance, intravenously. Ultrasonography examination evidenced an amorphous hyperechogenic structure, medial to the RE, with homogeneous echotexture, punctiform vascularization to amplitude Doppler (Power Doppler), measuring 2.8 cm in length and 1.4 cm in diameter, causing eyeball distortion and rejection. Based on ultrasonography results and with the patient still anesthetized, an incisional biopsy of the peribulbar mass was performed with a 5 mm disposable punch. The final CTVT diagnosis was possible after histopathological analysis. No more CTVT nodules were found, especially in the vulva, which had a prepubescent appearance, consistent with age. Treatment with 4 sessions of chemotherapy with vincristine sulfate resulted in complete remission of the tumor mass. In the second session, it was already possible to visualize the eyeball with a significant remission of the tumor mass, ruling out neoplastic exceresis. At this time, threat response, normal direct and consensual photopupillary reflexes, normal eyelid reflex, corneal surface without slit lamp biomicroscopy and fluorescein staining were present in the RE. Nevertheless, there were mild diffuse corneal edema and slight ciliary injection. One percent prednisolone eye drops (8/8 h) and tobramycin eye drops (6/6 h) were prescribed for 1 week. In the fourth session of chemotherapy, no changes were observed in the RE. Discussion: In the present case, the diagnosis of CPVD in a prepubertal patient, primary orbital TVTV, and the fact that the structure of the eye bulb and visual function remain intact, even with the significant volume of orbital neoplasia, are highlighted. A single report of skin CTVT in an 11-month-old prepubescent female dog was found. It is important to emphasize that CTVT is typically of dogs of reproductive age that have genital masses. Usually, extragenital masses are related to the act of licking, scratching, biting or sniffing the primary tumor (self-implantation), or rarely, by metastasis, a fact not observed in the present report, since the ocular mass was the only manifestation. Treatment was conducted according to indications of the literature. Four injections of vincristine sulfate were necessary, observing complete remission of the tumor mass with no relapse after 30 days. In this case report, it was possible to observe that CTVT may reveal unusual behaviors regarding epidemiology, which, added to the rare form of exclusively extragenital ocular clinical manifestation, impose a diagnostic challenge, making the histopathological examination an important tool for diagnosis.